AGE AS A DETERMINANT OF VERTEBRAL TRABECULAR BONE STATUS IN HODGKIN LYMPHOMA PATIENTS AFTER COMPLETION OF CHEMOTHERAPY: A PROSPECTIVE STUDY - Zhulkevich, I. V.; Yavorska, Yu. V. (Вісник наукових досліджень, 2015)
Bone density alterations are often reported in patients with solid tumors and hematologic malignancies except cases of Hodgkin lymphoma, when this problem remains understudied. The aim of this study was to investigate the significance of patients’ age and ABVD standard chemotherapy regimen as the determinants of vertebral trabecular bone tissue status changes. The study included 40 HL patients of different age groups (median age 35.38 ± 2.22). Densitometric and structural parameters were obtained from pre-treatment and after chemo CT scans. Analysis of these parameters after chemotherapy compared to the initial values revealed significant decrease of bone density (maximum up to 24.9 %) in all age groups, as well as in patients who were treated with ABVD regimen. Structural parameters values (BV/TV, SMI, BS, FD, textural parameters) had also suggested trabecular transformation dependent on patients’ age and chemotherapy treatment. Age and ABVD standard chemotherapy may be considered as predisposing risk factors for trabecular bone structural alteration and there is a need for timely diagnosis and prevention.